Fasal pengecualian liabiliti dalam kontrak pengguna di Malaysia - Sakina Shaik Ahmad Yusoff ,; Azimon Abdul Aziz ,; Suzanna Mohamed Isa, (Fakulti Undang - Undang, 2010)
Consumerism loaded with paternalistic ideals of protecting customers is by all means a paradigm shift from the so-called freedom of contract ideology. The aim of consumerism is to regulate and intervene in the market in their noble cause of upholding and empowering consumers in trade. Nevertheless in the area of exclusion of trader’s liability in consumer contracts, the move towards upholding consumer rights has been very minimal. Absence of appropriate legal mechanism in the form of a specific legislation to curb the use of unfair terms in consumer contracts has lead to oppression of consumers and the spread of unethical conduct of traders. In Malaysia however, the legal development in the area of exemption clauses in consumer contracts appears to be minimal. In the area of exemption of liability in Malaysia, by virtue of section 3 and 5 of the Civil Law Act 1956, the common law principles have been applied. However the case law development in Malaysia on exemption of liability, especially when the parties are of unequal bargaining power, causes a serious concern in consumer protection. This article explores the status of exemption clauses within the theoretical corpus of contract . It then examines the extent of the legal treatment on exemption clauses in consumer contracts as illustrated in reported cases